Morphoanatomy Characters, Protein and Chlorophyll Contents of Vanilla planifolia Jacks. ex Andrews Cuttings to Application of Natural Growth Regulators and Vegetable Elicitors: Morphoanatomy Characters of Vanilla planifolia (Biological Sciences - PJSIR, 2024)
This study aimed to examine the morphoanatomy characteristics, protein and chlorophyll contents of shoots on vanilla cuttings in response to application of natural growth regulators (NGR) and vegetable elicitors (VE). The study was conducted according to factorial design. The natural growth regulators included shallot extract 300 g/L (P1), banana weevil extract 300 g/L (P2), bamboo shoot extract 300 g/L (P3), coconut water 400 mL/L (P4) and sprouts extract 300 g/L (P5) and vegetable elicitors (E): Coleus scutellarioides extract (E1) and Amaranthus spinosus extract (E2) were used in the study. The results of the quantitative morphological characters showed that the highest shoot length (46.60 cm) was observed in P1E2, the number of leaves (7.67) in the P1E1, leaf length (8.25 cm) in P1E1, leaf width (2.82 cm) in P5E1 and stem diameter (0.87 cm) in P1E2 treatment, respectively. The quantitative and anatomical characters showed highly varied responses to different natural growth regulators and vegetable elicitors. The maximum stomatal pore length (29.22 µm), stomatal pore width (6.95 µm), stem cortex diameter (1039.02 µm) and leaf mesophyll (1565.97 µm) were recorded in P1E1, P5E1, P1E2 and P4E1, respectively. The highest mean protein and chlorophyll content (82.71 mg/Kg) and (2.69 mg/L) were observed in P1E1 and P1E2, respectively. The application of natural growth regulators and vegetable elicitors affects the morphoanatomy and increases vanilla plants' protein and chlorophyll content.